Study of supercontinuum generation from a mode-locked Erbium-doped fiber laser based on monolayer graphene saturable absorbe (2024)
ABSTRACT: We study the supercontinuum (SC) generation from a passively mode-locked erbium-doped fiber laser (ML-EDFL) using two different samples of monolayer graphene saturable absorber (SA) onto the side-polished surface of a D-shaped fiber, characterized with 98% and 65% polarization dependent loss (PDL), respectively. By using the first 98% PDL graphene SA (setup-1), output pulse spectral profile with 11.6 nm bandwidth was obtained from the ML-EDFL and subsequently amplified using an erbium-doped fiber amplifier (EDFA) to pump 2-m highly nonlinear fiber (HNLF) and 5-m ZBLAN lengths, both fibers operating at the normal dispersion regime, which resulted in individual SC generation of 350 and 245 nm, respectively. Furthermore, the EDFA was spectrally characterized by observing their SC blue shift of the central wavelength, reaching a value of 6.9 nm at 12 dB due to dispersion gain. With the second 65% PDL graphene SA (setup-2), we could generate SC with 227 and 351 nm bandwidths using 0.5 and 2 m HNLF lengths, respectively. Because the two SC setups were highly dependent on the polarization state of the input pulse, we optimized the SC generation from setup-2 using an external polarization controller (PC), which allowed us to adjust both the spectral brightness and the broadening of the SC.